Quantifying genetic variability and genotype ranking for food quality attributes in white Guinea yam (Dioscorea rotundata) using a multiple trait selection index - Olatunji, Alice Adenike; Gana, Andrew Saba; Tolorunse, Kehinde Dele; Matsumoto, Ryo; Adebola, Patrick; Asfaw, Asrat (Frontiers in Plant Science, 2025)
IntroductionYield and food product quality are important attributes in the selection of yam (Dioscorea spp.) cultivars. Among yam-based food products, boiled yam and pounded yam are traditional dishes that hold cultural, nutritional, and sensory significance in regions where yam is a staple food.Materials and methodsThis study evaluated the starch, sensory, and textural attributes of boiled and pounded yam products from 25 white Guinea yam (Dioscorea rotundata) genotypes grown across five environments. The sensory quality of both boiled and pounded yam products was assessed through sensory evaluation, while an instrument-based textural profile assay (ITPA) was conducted on pounded yam.Results and conclusionEnvironmental influences associated with cropping seasons and locations varied across traits, ranging from 1.4% (adhesiveness) to 20.7% (cohesiveness). Significant positive correlations (p <0.001) were observed between the overall acceptability of pounded yam and its aroma, taste, color, and appearance. Crude starch was positively correlated (p <0.001) with instrumental gumminess, chewiness, and resilience, but negatively with sensory texture, highlighting the need for balanced starch content. Using the log odds ratio analysis method, TDr1741073 was identified as a superior genotype. Similarly, the multi-trait genotype–ideotype distance index (MGIDI) highlighted it as outstanding in both attributes, making it a strong candidate for use as a parent in breeding programs.